Collection of medicinal plants as a base for the training of specialists in the field of pharmacy - Vasfilova, Evgeniya Samuilovna; Vorob'eva, Tat'yana Andreevna (Hortus botanicus, 2019)
The collection of medicinal and aromatic plants of the Botanical Garden of the Ural Branch of the Russian Academy of Sciences (Ekaterinburg) is actively used for the training of specialists with a higher and secondary specialized education in the field of pharmacy. The core of the collection consists of the species of scientific medicine in Russia (officinal), for which different organs are used for medical purposes (leaves, herbs, flowers, etc.). In this connection morphological groups of medicinal raw materials are distinguished. On the basis of the collection, most of the herbaric samples of medicinal plants and samples of medicinal raw materials are procured, which are used as training materials for practical classes during the academic year. Summer educational practice on pharmacognosy and students research work is conducted here.